2017
DOI: 10.1103/physrevb.95.085304
|View full text |Cite
|
Sign up to set email alerts
|

Lattice-matched heterojunctions between topological and normal insulators: A first-principles study

Abstract: Gapless boundary modes at the interface between topologically distinct regions are one of the most salient manifestations of topology in physics. Metallic boundary states of time-reversal-invariant topological insulators (TIs), a realization of topological order in condensed matter, have been of much interest not only due to such a fundamental nature, but also due to their practical significance. These boundary states are immune to backscattering and localization owing to their topological origin, thereby open… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 97 publications
0
7
0
Order By: Relevance
“…The results reproduce salient features of the electronic spectra in bulk and at surfaces, although there is some debate about whether many body corrections are necessary to obtain both the correct magnitude of the gap and its character (direct vs indirect) [14,17,18]. In the same spirit, existing studies of interfaces either consider lattice matched cases [19] or make a priori assumptions about structural changes at the boundary, such as fixing the inter-QL distance to its experimental value [20].…”
Section: Introductionmentioning
confidence: 90%
“…The results reproduce salient features of the electronic spectra in bulk and at surfaces, although there is some debate about whether many body corrections are necessary to obtain both the correct magnitude of the gap and its character (direct vs indirect) [14,17,18]. In the same spirit, existing studies of interfaces either consider lattice matched cases [19] or make a priori assumptions about structural changes at the boundary, such as fixing the inter-QL distance to its experimental value [20].…”
Section: Introductionmentioning
confidence: 90%
“…For instance, it has been predicted that a hybrid structure made of a 3D TI and a superconductor can produce a superconducting proximity effect at the interface, which might lead to the emergence of two-dimensional (2D) topological superconductivity hosting Majorana fermions. , In graphene transferred on 3D TI, a strong proximity effect can induce opening of the band gap and strong spin–orbit coupling (SOC), which leads to a strong tunability and suppression of the spin signal and lifetime. , There has been some research on the topological proximity effect between a normal insulator and a topological insulator (NI/TI). Previous calculations and experiments have indicated that a Dirac state exists at the NI/TI interface because of the proximity effect caused by TIs. In addition, predictions of such an interaction with non-topological states at the NI/TI interface might result in vertical twinning of the Dirac cone; the non-topological states can acquire spin texture without magnetic doping . The group-V single-element monolayer with a band gap ranging from 0.36 to 2.62 eV on a TI is an ideal platform for the study of the topological proximity effect at a NI/TI interface. , In particular, the band structure on a 2D NI/3D TI can be directly probed with angle-resolved photoemission spectra (ARPES).…”
Section: Introductionmentioning
confidence: 99%
“…There have been many efforts recently to understand the phenomena at the interface of a TI with different materials, e.g. metals, conventional insulators [10,11], as well as other materials [4,12,13]. It has also been demonstrated experimentally that the surface bands of the TI can be modulated by modifications of the surface [5].…”
Section: Introductionmentioning
confidence: 99%